Optimization Study of Syngas Production from Catalytic Air Gasification of Rice Husk - Minh Loy, A.C. (Insight Society, 2020)
Catalytic air gasification of rice husk was investigated in this study to optimize the hydrogen and syngas composition using a thermogravimetric analyzer coupled with a mass spectrometer. Then, a fixed bed reactor is used as a pilot plant to evaluate the practicality of the optimum parameters obtained from thermogravimetric analyzer test for upscaling. The catalyst used is coal bottom ash selected based on a previous study and obtained from a local power plant. The results from thermogravimetric analyzer test had shown that the optimum input parameters for syngas composition were at a reaction temperature of 900 Â°C, rice husk particle size of 250 Î¼m, amounts of catalyst of 10 wt, and air to biomass ratio of 1.25 to obtain product gas with 73.8 vol of syngas composition. From a fixed bed reactor, 76.2 vol of syngas composition is obtained, 3.25 higher than the previous test. Furthermore, 84.1 wt of gaseous product yield, included syngas and CH4, was obtained in the catalytic air gasification using a coal bottom ash catalyst. This showed the potential of coal bottom ash as the substitute for commercial catalysts in catalytic gasification. Lastly, principle component analysis was applied to evaluate the effect of temperature, particle size, air to biomass ratio, and coal bottom ash loading on H2 and syngas production. H2 production appears to be highly sensitive to the reaction temperature. Meanwhile, particle size, air to biomass ratio and catalyst loading were having a positive correlation with CO2 and CH4 but negative correlation with H2. Â© 2020, International Journal on Advanced Science Engineering Information Technology.